2019
DOI: 10.1140/epjst/e2019-800222-7
|View full text |Cite
|
Sign up to set email alerts
|

Antimonotonicity and multistability in a fractional order memristive chaotic oscillator

Abstract: A memristor diode bridge chaotic circuit is proposed in this paper. The proposed oscillator has only one nonlinear element in the form of memristor. Dynamical properties of the proposed oscillator are investigated. The fractional order model of the oscillator is designed using Grünwald-Letnikov (GL) method. Bifurcation diagrams are plotted which shows that the proposed oscillator exhibits multistability. Finally, the antimonotonicity property of the fractional order oscillator is discussed in detail with two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Multistability signifies the coexistence of attractors in a dynamical system for the same parameter values [33]. In recent years, there is great research on chaotic and hyperchaotic systems with multistability in the literature [34][35][36]. In this work, we show that the new hyperchaotic system exhibits multistability with three coexisting attractors for three different initial conditions.…”
Section: Introductionmentioning
confidence: 71%
“…Multistability signifies the coexistence of attractors in a dynamical system for the same parameter values [33]. In recent years, there is great research on chaotic and hyperchaotic systems with multistability in the literature [34][35][36]. In this work, we show that the new hyperchaotic system exhibits multistability with three coexisting attractors for three different initial conditions.…”
Section: Introductionmentioning
confidence: 71%
“…It was well established in the literature that fractional-order analysis can very well match real-time systems [16][17][18][19]. It was shown that models with memory can be effectively modelled using fractional calculus and we could explore some complex dynamical properties when using fractional-order analysis [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 94%
“…Memristors, describing the missing relationship between charge and magnetic flux, are consider as the fourth type of electronic components in addition to resistors, capacitors and inductors [10]. Due to their strong nonlinearity, nanometer size, low power consumption and unique memory characteristics, memristors have been employed to construct chaotic systems [11,12], which can exhibit rich nonlinear dynamical behaviors, such as multi-scroll attractors [13,14], antimonotonicity [15], hidden extreme multistability [16,17] and hyperchaotic phenomena [18]. In addition, memristors play an important role in studying neuron dynamics.…”
Section: Introductionmentioning
confidence: 99%